Childhood in a Global Perspective - Wells Karen (Policy Press, 2009)
This book offers a unique global perspective on children's lives throughout the World. Childhood in a Global Context, Policy and Practice, Race and Class and Gender, Children and Families, School and Work, Children and Politics, Children and Youth at War, Rescuing Children and Children's Rights, Bibliography, Index.